Analyzing the influence of moral culture and job satisfaction on organizational commitment in enhancing employee performance: an empirical study at PT. Antam TBK Gold Mining Business Unit Pongkor - Indupurnahayu; Muhamad Azis Firdaus; Maryani; Sapie Bin Sabilan (Technium Business and Management, 2022)
This research aims to analyze the influence of moral culture, organizational commitment, and job satisfaction on employee performance, as well as the influence of moral culture and job satisfaction on organizational commitment. Data were collected through questionnaires from 154 respondents from PT ANTAM UBPE Pongkor and analyzed using Partial Least Square (PLS) based on Structural Equation Model (SEM) with SmartPLS 3.0. The results of the analysis show that moral culture, organizational commitment, and job satisfaction significantly and positively influence employee performance, and moral culture and job satisfaction also significantly and positively influence organizational commitment.